2017
DOI: 10.1016/j.stem.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Markers Guide Differentiation to Improve Graft Outcome in Clinical Translation of hESC-Based Therapy for Parkinson’s Disease

Abstract: SummaryStem cell treatments for neurodegenerative diseases are expected to reach clinical trials soon. Most of the approaches currently under development involve transplantation of immature progenitors that subsequently undergo phenotypic and functional maturation in vivo, and predicting the long-term graft outcome already at the progenitor stage remains a challenge. Here, we took an unbiased approach to identify predictive markers expressed in dopamine neuron progenitors that correlate with graft outcome in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
310
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(338 citation statements)
references
References 35 publications
23
310
3
2
Order By: Relevance
“…Recently, Kirkeby et al . found that EN1+ progenitors transplanted in animal models resulted in grafts rich in DA yield and density52. The fact that both FOXA2 and EN1 are robustly maintained in 3D differentiation, but not as effectively in 2D, may indicate that the former are primed for long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kirkeby et al . found that EN1+ progenitors transplanted in animal models resulted in grafts rich in DA yield and density52. The fact that both FOXA2 and EN1 are robustly maintained in 3D differentiation, but not as effectively in 2D, may indicate that the former are primed for long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Developing GMPcompliant cell-manufacturing processes not only entails the use of appropriate starting cell lines and media components, but also requires monitoring and reduction of variability in cell fate at each step -so that a uniform cell product can be produced with each differentiation round. In such efforts in my own laboratory, we observed significant batch-to-batch variation in how many DA neurons are ultimately produced from FOXA2/LMX1A-expressing progenitors after transplantation and functional maturation in vivo (Kirkeby et al, 2017a). This observation was puzzling as, based on what was known about development at the time, these progenitors should all form mature midbrain DA neurons.…”
Section: From Hescs To Therapeutic Da Neuronsmentioning
confidence: 99%
“…However, a parallel study based on single cell sequencing of the midbrain Lmx1a-expressing progenitors during mouse development revealed that FoxA2 and Lmx1a (as well as most other ventral midbrain markers commonly used to detect the DA progenitor population prior to grafting) are also co-expressed in early diencephalic progenitors that form the subthalamic nucleus (STN), and therefore do not exclusively identify the midbrain DA neuron domain (Kee et al, 2017). Thus, cells expressing FOXA2/LMX1A can give rise to two types of neurons, and the relative proportion of these can now be tracked and controlled using the predictive markers identified that are specifically expressed in the DA domain (Kee et al, 2017;Kirkeby et al, 2017a). This allowed us to better control stem cell differentiation in vitro by adding FGF8 to sufficiently caudalize the cells such that DA (and not STN cells) are formed with a high yield and purity (Kirkeby et al, 2017a).…”
Section: From Hescs To Therapeutic Da Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study aiming at identifying markers to predict the yield of DA neurons in transplant showed that the commonly used DA neuron markers (FOXA2, LMX1A and CORIN) poorly correlate with DA neuron production in vivo whereas the markers of caudal ventral midbrain (FGF8, PAX5, EN2 and CNPY1 (Canopy FGF signaling regulator 1)) are associated with higher DA neuron yield. Addition of FGF8 later than day 9, but not earlier (before day 9), maintains the FOXA2/LMX1A/B expression in progenitors and increases the generation of DA neurons (Kirkeby et al, 2016). This result suggests that FGF8 promotes DA neuron program by patterning the progenitors to the caudal fate at a late stage.…”
Section: Neuronal Differentiation and Functional Maturationmentioning
confidence: 99%